Factors Associated With Glycemic Control In Patients With Type 2 Diabetes In Tamale Teaching Hospital In The Northern Region Of Ghana - Masoom, A.M. (University Of Ghana, 2022)
ABSTRACT Introduction: Diabetes Mellitus (DM) continues to be a major public health concern with enormous effects on human health, living standards, the economy, and health care systems. People are at risk of this disease due to lifestyle factors such as alcohol drinking, smoking cigarettes/tobacco, and not exercising regularly during their youth. In Ghana, there is limited evidence of factors such as alcohol drinking, smoking cigarette, and regular exercise associated with glycemic control in patients with type 2 diabetes mellitus attending the Tamale Teaching Hospital in the Northern Region of Ghana. Objective: The main objective of the study was to determine the proportion of glycemic control and associated factors among patients with type 2 diabetes mellitus attending the Tamale Teaching Hospital in the Northern Region of Ghana. Method: An analytical cross-sectional study involving patients with type 2 diabetes mellitus was conducted at the Tamale Teaching Hospital in the Northern Region of Ghana. The simple random sampling technique was used to select patients in the diabetes clinic in the Tamale Teaching Hospital in the Northern Region of Ghana. Questionnaires were administered to these patients and data on the proportion of glycemic control and associated factors were collected. The proportion of glycemic control in patients with type 2 diabetes mellitus was assessed by using the frequency and percentages. The association between glycemic control in patients with type 2 diabetes mellitus and the independent variables (socio-demographic and lifestyle related factors) were tested using Pearson‘s Chi-square test and Fisher‘s Exact test. The univariate and multivariable logistic regression were performed to determine the association between the glycemic control in patients with type 2 diabetes mellitus and various independent variables at 5% significance level. Results: The proportion of poor glycemic control in patients with type 2 diabetes was 47.3%(95% CI=42.0% -52.7%). Major risk factors identified to have influenced poor glycemic control in patients with type 2 diabetes were 60 years and above age group ( ), family history of diabetes ( ), former alcohol drinkers ( ), andformer cigarette/tobacco smokers( ). The protective factors identified to have influenced poor glycemic control in patients with Type 2 diabetes were urban residents( ) and regular physical exercise ( ). Conclusions and Recommendations: This study concludes that type 2 diabetes patients attending the diabetes clinic of the Tamale Teaching Hospital have moderate glycemic control. Major risk factors such as age, family history of diabetes, alcohol consumption, smoking cigarette, and protective factors such as living in urban areas and regular physical exercise were associated with glycemic control in patients with type 2 diabetes. The author recommends that the in charge of the diabetes clinic at the Tamale Teaching Hospital in the Northern Region should appoint some health workers who will routinely check the patients' records to identify patients with HbA1c≥ 7% in order to take the appropriate actions. This monitoring of patients' HbA1c will enhance patient glycemic control and improve better adherence to medication which will result in good quality of life. The author also recommends that health workers such as doctors and nurses at the hospital, during consultation, should continue to advise patients on lifestyle modifications such as reducing alcohol drinking and smoking cigarette/tobacco, and performing more regular exercises. This will increase their general well-being and promote their quality of life.
MA. Public Health
Keywords: Glycemic; Type 2 Diabetes; Tamale Teaching Hospital; Northern Region Of Ghana